2020
DOI: 10.1097/bsd.0000000000000990
|View full text |Cite
|
Sign up to set email alerts
|

Readmission Rate After 2-level Lumbar Decompression

Abstract: Study Design: Retrospective review of the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database years 2012–2015. Objective: Compare the 30-day readmission and postoperative major complications rates of 2-level lumbar decompression performed in the ambulatory and the inpatient settings. Summary of Background Data: In recent years, there is an increasing trend toward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…The overall readmission rate for patients undergoing elective isolated lumbar decompression in our study was at or below the rate previously reported in literature 52–59 . However, readmission data in large databases such as NSQIP often lack granularity with regard to the cause of readmission and such classification is subject to the clinical reviewer for each hospital 60 .…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The overall readmission rate for patients undergoing elective isolated lumbar decompression in our study was at or below the rate previously reported in literature 52–59 . However, readmission data in large databases such as NSQIP often lack granularity with regard to the cause of readmission and such classification is subject to the clinical reviewer for each hospital 60 .…”
Section: Discussioncontrasting
confidence: 51%
“…[48][49][50][51] The overall readmission rate for patients undergoing elective isolated lumbar decompression in our study was at or below the rate previously reported in literature. [52][53][54][55][56][57][58][59] However, readmission data in large databases such as NSQIP often lack granularity with regard to the cause of readmission and such classification is subject to the clinical reviewer for each hospital. 60 As such, surgically related readmission rates of large databases may be inflated and percentages may better reflect an all-cause readmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are increasingly performed in an ambulatory or day-care setting. Inadequate pain management is one of the main reasons for delayed discharge or readmission after surgery [1,4]. Effective pain control improves post-operative outcomes and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%